Suggestive hypothesis on a case report: Patient presenting with cyclical ovarian cysts coupled to increased cholestatic enzymes. Issue 2 (4th November 2018) - Conca, Paolo; Cafaro, Giovanni; Savastano, Silvia; Coppola, Antonio; Cimino, Ernesto; Tarantino, Giovanni
Abstract: We describe the case of a childbearing‐age woman presenting with spontaneous recurrent functional ovarian cysts and, more interestingly, chronic and asymptomatic elevation of cholestatic parameters. The patient showed no history of chronic viral infections, immunological and metabolic disorders, alcohol abuse and environmental toxins exposition. Hepatic ultrasonography and cholangio‐pancreatography‐magnetic‐resonance excluded any morphological and structural abnormalities, while liver biopsy evidenced only minimal and not specific features of inflammation. Cholestasis indices obtained prompt recovery after each cycle of synthetic hormone therapy, implanted to treat functional ovarian cysts. She has continuously experienced the off‐therapy asynchronous recurrence of liver laboratory abnormalities and functional ovarian cysts. The favorable effect of the synthetic hormone therapy to obtaining a stable recovery of this unexplained long‐lasting cholestatic syndrome could be likely explained by downregulation of an endogenous ovarian overproduction, although estrogen‐regulated local intracellular transduction pathways cannot be excluded.